Brain Computer Interface based Emotion Recognition Using Fuzzy Logic - V., purushothaman.; S., Sivasaravanababu.; P., keerthana.; J., lavanya; S, vishalni.; M, yuvarani. (International Journal of Engineering and Technology, 2018)
A brain controlled robot based on Brainâ€“computer interfaces (BCI). BCIs are systems that can bypass conventional channels of communication (i.e., muscles and thoughts) to provide direct communication and control between the human brain and physical devices by translating different patterns of brain activity into commands in real time. With these commands a mobile robot can be controlled. The intention of the project work is to develop aÂ robot that canÂ assist the disabled people in their daily life to do some work independent on othersIn Brain computer interface has one electrode by wearing that band we got some ParametersÂ EEG (electroencephalograph)wave. Based on the Neuron Movement it will work. And then, a fusion algorithm. The most visible EEG changes appear within the first two seconds following stimulation. The rhythm increase most significantly in the negative emotional state Level analyzer unit (LAU) will receive the brain wave raw data and it will extract and process the signal using Mat lab platform. With this entire system, we can move a robot according to the human thoughts and it can be turned by blink muscle contraction these both outputs are fed to compare both output to fuzzy logic.Â Â